The NA60+ experiment at the CERN SPS - Siddhanta Sabyasachi (EPJ Web of Conferences)
NA60+ is a new experiment designed to study the phase diagram of the strongly interacting matter at high baryochemical potential from 200 to 550 MeV at the CERN SPS. It is focused on precision studies of thermal dimuons, heavy quark and strangeness production in Pb–Pb collisions at center of mass energies ranging from 6 to 17 GeV. This contribution is focussing on the experimental apparatus, including the technical aspects and the R&D status, as well as the physics program and its competitiveness and complementarity to other experiments.